2019
DOI: 10.1155/2019/3832790
|View full text |Cite
|
Sign up to set email alerts
|

Airport Entry and Exit Screening during the Ebola Virus Disease Outbreak in Sierra Leone, 2014 to 2016

Abstract: We present entry and exit screening outcomes on all persons passing through Freetown International Airport (FNA) in Sierra Leone during the period 1st September 2014 to 4th February 2016. A total of 166,242 persons underwent screening for Ebola Virus Disease (EVD) at FNA. Five persons were denied air travel from Sierra Leone after secondary screening. Laboratory testing revealed none were positive for EVD. No cases were identified through entry screening route. The public health value of airport screening for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Although fever is a primary symptom in the majority of infectious diseases, many studies have demonstrated that measuring body temperature alone is insufficient in detecting infections. 12 , 13 , 60 70 , 75 79 As has been suggested previously, in addition to body temperature, heart rate and respiratory rate are the two crucial vital signs needed to be monitored. 75 79 Additionally, since many infectious diseases, especially coronavirus related infections, cause SARS, monitoring breathing related parameters may enhance sensitivity and specificity of disease screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fever is a primary symptom in the majority of infectious diseases, many studies have demonstrated that measuring body temperature alone is insufficient in detecting infections. 12 , 13 , 60 70 , 75 79 As has been suggested previously, in addition to body temperature, heart rate and respiratory rate are the two crucial vital signs needed to be monitored. 75 79 Additionally, since many infectious diseases, especially coronavirus related infections, cause SARS, monitoring breathing related parameters may enhance sensitivity and specificity of disease screening.…”
Section: Discussionmentioning
confidence: 99%
“… 17 19 Several studies were also included that analyzed the impact of a controlled environment on screening accuracy. 21 , 57 59 For literature evaluating the efficiency of IRT screening for the detection of febrile international travelers, seventeen studies were identified: one aimed at detecting SARS in Canada; 60 four studies for Dengue detection in Taiwan; 12 , 13 , 61 , 62 five for Influenza in New Zealand, 63 , 64 Japan, 65 , 66 and Australia; 67 and three for Ebola virus disease (EVD) in the USA, Australia, and the UK, 68 and Sierra Leone; 69 , 70 one for MERS in Indonesia; 71 and three for COVID-19 in multiple countries. 72 74 For literature evaluating the detection of infectious diseases with measurements of vital signs, three studies were identified containing the required information for inclusion: two utilizing CMOS camera that was equipped with IRT; 75 , 76 two utilizing Doppler blood-flow meter, 10-GHz microwave radar, and thermography; 77 , 78 and one utilizing radar, finger-tip photoreflector, and thermography.…”
Section: Methodsmentioning
confidence: 99%
“… 8 The measurement of fever as a means of identifying infected individuals at ports of entry into countries became more widespread during the 2013–2016 outbreak of the Ebola virus disease in West Africa. 9 , 10 However, for a disease like COVID-19, where most cases may remain asymptomatic, 8 , 11 , 12 screening for infected individuals by temperature measurement alone may not be the most effective approach. This is because all the 1030 travellers who were quarantined in Accra had been initially screened at the airport for fever and were all found to be non-febrile.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature screening at airports was encouraged by West African public health authorities during the 2014-2016 Ebola epidemic to control the transmission of the virus. These temperature screenings allowed the prevention of those who might be febrile from travelling, and thus were part of a co-ordinated attempt to limit the transmission of the virus 8,26 . This kind of mass transport, community-based, and even at-home temperature screening has also been integral to global containment efforts during the current COVID-19 pandemic 16,27 .…”
Section: Temperature As a Vital Signmentioning
confidence: 99%